The Impact of Corporate Governance on Quality of Risk in China - Huang, Liyimeng (2017)
This dissertation aims to investigate the impact of corporate governance on quality of risk disclosure in China. Based data on 154 firm-year observations (77 non-financial firms over 2 years), the current study find the evidence for the relationship between corporate governance and quality of risk disclosure. In addition, further analysis finds that effects of industry and year affect the connection between corporate governance and risk disclosure. This dissertation contributes to accounting literature by studying mechanisms of corporate governance in China in the aspect of quality of risk disclosure. The present study endows Chinese external investors with a new method of understanding the internal risk of companies from annual report. Therefore, the investors are able to make decisions on investment more reasonably. In addition, this dissertation implies the connection between corporate governance and quality of risk disclosure, and provides evidence to approve the results of some prior literature.